انسانی حقوق کا عالمی منشور اور مقاصد الشریعہ: ممکنہ ہم آہنگی کے امکانات کا تجزیاتی مطالعہ: The Universal Declaration of Human Rights and Maqasid al-Shari’ah: An Analytical Study of Potential Convergences (Contemporary Journal of Social Science Review, 2025)
The contemporary global discourse on human rights is marked by a profound conceptual encounter between the secular framework of the Universal Declaration of Human Rights (UDHR) and the divinely-rooted objectives of Islamic law (Maqāṣid al-Sharīʿah). This study explores the nature, depth, and implications of both convergence and contention between these two monumental paradigms.  While the UDHR emerged as a post-World War II moral response to Western atrocities and remains grounded in human reason and secular consensus, Maqāṣid al-Sharīʿah represents a comprehensive, theologically anchored system aimed at preserving faith, life, intellect, progeny, and wealth. The research demonstrates striking areas of harmony in the shared commitment to human dignity, justice, life protection, education, and property rights—values that reflect the universal moral intuitions embedded in fitrah۔Yet, irreconcilable divergences persist, particularly concerning the source of legislative authority (divine sovereignty versus popular sovereignty), the boundaries of religious freedom (especially apostasy), gender roles and family law, and the relationship between morality and legislation. These tensions are not merely legal but existential, reflecting two fundamentally different visions of the human being, society, and ultimate purpose.  Drawing on classical and contemporary Muslim scholarship—including al-Shāṭibī, al-Ghazālī, Yūsuf al-Qaraḍāwī, Ṭāhā Jābir al-ʿAlwānī, and Abdullahi Ahmed An-Naʿim—the study proposes pathways to reconciliation through a Maqāṣid-centred approach, historical contextualization of the UDHR, inter-civilizational dialogue, and emphasis on shared ethical foundations. Rather than demanding compromise of principles, it advocates a confident, wisdom-based engagement that presents Islamic law as the fuller realization of universal human aspirationsThis work is confined to theoretical and normative comparison, deliberately excluding country-specific case studies or detailed legal codifications. It ultimately argues that genuine harmony is possible—not through dilution, but through the rediscovery of Maqāṣid as a dynamic framework capable of transcending apparent contradictions while remaining faithful to divine wisdom.